2003
DOI: 10.1002/acp.879
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a prior cognitive interview on children's acceptance of misinformation

Abstract: This research examined whether a Cognitive interview facilitates correct recall in children aged 4 to 5 and 9 to 10 years, and whether a Cognitive interview given before post-event misinformation reduces children's reporting of suggestions on subsequent memory tests. Children were presented with an event followed the next day by a Cognitive or a Memorandum interview. Children were then read a post-event summary containing misleading suggestions. The next day all children were given both standard test and modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
68
2
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 35 publications
5
68
2
3
Order By: Relevance
“…The results showed that the IMS interviews were as good as the Standard verbal interviews on almost all accuracy measures, i.e., Total Accuracy, People Accuracy, Action Accuracy, and Description Accuracy. The mean accuracy for all accuracy measures in the IMS interviews was high, which is in line with previous research using aids together with the best practice components, such as ground rules and open-ended questions (Dorado & Saywitz, 2001;Hershkowitz et al, 2001;Holliday, 2003;Memon et al, 2010). The only exception was Object Accuracy, which was significantly better in the Standard verbal interviews where it was very high, 0.98; in addition, even though the difference between the methods was significant, the mean Object Accuracy in the IMS interviews was still 0.88.…”
Section: Discussion the Accuracy And Completeness Of Children's Statesupporting
confidence: 89%
See 2 more Smart Citations
“…The results showed that the IMS interviews were as good as the Standard verbal interviews on almost all accuracy measures, i.e., Total Accuracy, People Accuracy, Action Accuracy, and Description Accuracy. The mean accuracy for all accuracy measures in the IMS interviews was high, which is in line with previous research using aids together with the best practice components, such as ground rules and open-ended questions (Dorado & Saywitz, 2001;Hershkowitz et al, 2001;Holliday, 2003;Memon et al, 2010). The only exception was Object Accuracy, which was significantly better in the Standard verbal interviews where it was very high, 0.98; in addition, even though the difference between the methods was significant, the mean Object Accuracy in the IMS interviews was still 0.88.…”
Section: Discussion the Accuracy And Completeness Of Children's Statesupporting
confidence: 89%
“…Previous research indicates that children as young as 4 years of age can provide reliable and valid information when interviewed properly (Holliday, 2003;Lamb et al, 2007), and when age differences are seen they concern mainly the amount of information that children can provide. For example, Hershkowitz et al (2012) investigated finer age differences in patterns of response and found that 3-and 4-year-olds were less capable than 5-and 6-year-olds in providing informative and detailed statements.…”
Section: Discussion the Accuracy And Completeness Of Children's Statementioning
confidence: 99%
See 1 more Smart Citation
“…This design allowed us to determine whether building rapport can act as a safeguard against reporting previously presented misinformation in adult witnesses. Recent research utilizing similar paradigms with child witnesses found that the use of cognitive interviewing including rapport-building reduced the amount of false acquiescence to leading information provided by the interviewer but that an extended rapport phase did not increase the amount of correct details reported or reduce the likelihood of reporting misinformation (Holliday, 2003;Holliday & Albon, 2004).…”
Section: Rapport-building and Adult Witnessesmentioning
confidence: 99%
“…The effects of some of these verbally oriented protocols have been investigated in relation to the accuracy of children's memory (Granhag & Spjut, 2001;Holliday, 2003a;Holliday, 2003b). Several countries have adopted a specific verbal interview protocol as the national standard for child forensic interviews (e.g., the NICHD protocol is used in Israel).…”
Section: Interviewing Strategiesmentioning
confidence: 99%